IMPROVING STUDENTS’ VOCABULARY USING POSTER MEDIA FOR SECOND GRADE HEARING DISABLE AT SMALB - Iis Siti Sa'adah; Ani Atikah (PROJECT (Professional Journal of English Education), 2019)
The objective of the study is to improve vocabulary in children with special need. The researchers have chosen the object in the school because, the school has lack of learning media and teachers. This research used the "Poster" as a media, in addition the poster can make the students more interest to learn. The researchers using Poster media with a carton paper converted into a tree viewer and students are required to fill in a blank section of the tree shape based on a pre- existing question on the poster containing the Vocabulary subject Noun and Verb. Vocabulary with visuals so that they are easier to learn which tend to be limited by the ability they (deaf students) have. The researchers used Class room Action Research (CAR).The steps in action research (planning, action, observation, and reflection) are done in a cycle. This method is one of the active learning strategy by involving students to always study English learning especially The results of this research showed that the poster media can improve the vocabulary of the students and the students more interested to learn vocabulary.Keywords: Vocabulary Understanding, Deaf, poster Media